Anemia Development and Retrospective Evaluation of Blood Transfusions in Patients in Anesthesia Intensive Care Unit - Bulut, Oguz Kagan; Bepstaps, Azize; Bayindir, Serpil; Bolat, Esef; Akel, Ramazan; Demirel, Ismail (Galenos Publ House, 2025)
Objective: Anemia is a common problem of critically ill patients in intensive care units (ICU). This retrospective single-center study. We aimed to investigate the incidence of anemia and transfusions, transfusion-related risks, and clinical outcomes. We also investigated the contribution of the amount of blood taken for diagnosis and follow-up purposes to anemia. Materials and Methods: In this retrospective single-center study (01.01.2015-31.12.2015), patients aged 18 years and older who were hospitalized for more than 24 hours were divided into two groups male (Group E) and female (Group K) and compared. The first 30-day hemoglobin (Hb) values, Hb values before and after transfusion, daily blood losses, and fluid balance, indications for transfusion, and related complications, and the number of erythrocyte suspensions used were recorded. Results: Anemia was present in 60.7% and 83.9% of the patients on day 1 and day 3. Anaemia developed on the 3rd day in 55.6% of non-anemic patients. The mean Hb before transfusion was 7.5 +/- 1.3 g/dL and the mean Hb after transfusion was 6.9 +/- 1.1 g/dL. We found that the acute physiology and chronic health evaluation II score was higher in patients who received transfusion, and mortality was higher in female patients. On the 1st day of hospitalization, a mean of 37.0 +/- 15.7 mL/person blood sample was taken; due to repeated blood samples (mean 147.2 +/- 117.1 mL), we found that Hb values decreased significantly to require blood transfusion. Conclusion: It was found that the majority of the patients admitted to the ICU were anaemic. Hb values continued to decrease over time. Repeated blood sampling contributed to the development of anaemia. Febrile reaction was the most common transfusion-related complication. It was concluded that practices in accordance with the current universal transfusion guidelines were performed.
Keywords: Anemia; blood transfus & imath;on; intensive care unit